IMPLEMENTASI MODEL PEMBELAJARAN BERBASIS MASALAH DALAM MENULIS TEKS EKSPLANASI PADA KELAS XI SMK MUHAMMADIYAH 3 KARANGANYAR - Risqina Aprilia Nur Fariza; Atiqa Sabardilla (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2023)
The purpose of this study is to use a problem-based learning paradigm to help students at SMK Muhammadiyah 3 Karanganyar who have difficulty with the subject matter to compose an explanatory text. Qualitative descriptive method was used for this research. Teachers and students of grade 11 SMK Muhammadiyah 3 Karanganyar were interviewed for this study. The data of this research include: teachers plan problem-based learning models in the form of lesson plans in accordance with the curriculum; a teacher applies a problem-based learning model according to the syntax; a teacher encountered a problem when using a problem-based learning model to ask students to write an explanatory text. Keywords: implementation, problem-based learning, explanatory text